Control of electric power generation of thermal power plant in TamilNadu. (September 2018) - Murshitha Shajahan, M.S.; Najumnissa Jamal, D.; Aparna, V.; Ahamed Khan, M.K.A.
Abstract: A control configuration for controlling the generated power in NLC TamilNadu Power Limited (NTPL) thermal power station by manipulating the coal flow rate, air flow rate and feed water flow rate is proposed here. Real Time data from NTPL thermal power station unit-Tuticorin unit of 500 MW capacity is recorded over an interval of time. This real-time data is used to model the coal flow rate, air flow rate and feed water flow rate loops which will be controlled to eventually control the generated power. The controller for the three loops is tuned using evolution and optimization techniques like genetic algorithm (GA) and Particle Swarm Optimization (PSO). Results of the controller tuned using both the techniques are provided and they are compared with each other. From the simulation results, it can be emphasized that the controller performs fairly well in servo and regulatory configurations.